Prevalence of common claw lesions of lameness in cattle and buffaloes of central Punjab region of India - SINGH, SWARAN; DUA, K; SINGH, S S; DHAND, N (The Indian Journal of Animal Sciences, 2016)
Prevalence of lameness was estimated in crossbred lactating cattle (337) and Murrah buffaloes (82) from 7 organised dairy farms and 100 lactating cattle and 51 lactating buffaloes from 50 unorganised (backyard) farms from different villages of Ludhiana district of Punjab. Gait of each animal was first assessed on a 5- point numerical scale on the day of observation. Clinical lameness was significantly more in crossbred cattle (8.92%) as compared to buffaloes (2.26%) and was more on organised farms (9.31%) as compared to unorganised farms (1.99%). Each animal was then examined for any claw lesion before and after removing sliver of 1mm from the solar surface. Most of the lesions were observed in hind claws [OR:1.17] except sole avulsions (OR:0.25) and white line fissures (OR:0.37) which were more evident in fore claws. Heel erosions (45.44%), sole haemorrhages (2.26%), white line haemorrhages and under run soles (4.56%) were predominant lesions of lameness in organised dairy farms especially crossbred cattle suggesting claw horn disruption as the possible aetiology. Sole avulsions (37.37%), white line fissures (13.37%), overgrown hooves (10.53%) and overgrown soles (6.75%) were more frequent on unorganised farms suggesting poor hoof synthesis due to trace mineral deficiency. Overgrown hoofs were more frequent in buffaloes. Sole avulsions were observed for the first time in this study.